REBECKA TAVES SHEFFIELD, Documenting Rebellions: A Study of Four Lesbian and Gay Archives in Queer Times - Seller, Shyla (Archivaria, 2021)
Documenting Rebellions: A Study of Four Lesbian and Gay Archives in Queer Times. Rebecka Taves Sheffield. Sacramento: Litwin Books, 2020. 272 pp. 987-1-63400-091-8